"A reward for surviving the day": Women professionals' substance use to enhance performance. Issue 2 (June 2022) - Kiepek, Niki; Beagan, Brenda; Ausman, Christine; Patten, San
Abstract: Introduction: This study was undertaken to explore the use of substances by professionals in Canada. A non-problem-focussed approach informed study design, with participants recruited outside treatment programs or professional monitoring programs and data collection including indicators of 'positive' or desired effects. Methods: Participants were 19-years or older and residing in Canada. An anonymous online survey ( n  = 515) collected information about demographics, prevalence of substance use, substances previously used, and mental health. Interviews ( n  = 52) focused on personal use of substances and effects, perspectives on professional regulation of substance use, and experiences around disclosure. Results: Gender patterns were similar for use of licit and illicit substances, while women reported using greater numbers of pharmaceuticals and higher use of substances targeted at improving mood, decreasing pain, and improving sleep. Men and women discussed volition regarding choices around substance use and described substances as contributing to improved productivity and mood. Whereas men discussed stressors as occurring outside the home, with 'home' being a place to return to and unwind, women are predominantly responsible for coordinating family activities and events and saw both work and social spaces as stressful. Women's use of substances was subject to social scrutiny intertwined with normative ideals around mothering, pregnancy, and breastfeeding. Substance use occurs in the context of 'busy' lives, where people have little time and energy for other healthy lifestyle alternatives; as one participant explained, substance use is "a reward for surviving the day." Discussion: In the West, societal expectations continue to attribute predominant responsibility for parenting to women, where being a 'good mother' requires one to be a 'happy mother' and experiences of distress are silenced. Women strive to attain the status of an 'ideal worker' while balancing multiple roles and responsibilities. Substances are a means to instantaneously enhance individual performance and pleasure in response to troubling social structures and systems that remain largely unchallenged.